2014
DOI: 10.1038/srep04200
|View full text |Cite
|
Sign up to set email alerts
|

Probing of 2 dimensional confinement-induced structural transitions in amorphous oxide thin film

Abstract: Whereas the atomic structure of surface of crystals is known to be distinct from that of bulk, experimental evidence for thickness-induced structural transitions in amorphous oxides is lacking. We report the NMR result for amorphous alumina with varying thickness from bulk up to 5 nm, revealing the nature of structural transitions near amorphous oxide surfaces/interfaces. The coordination environments in the confined amorphous alumina thin film are distinct from those of bulk, highlighted by a decrease in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 35 publications
4
34
0
Order By: Relevance
“…In systems containing Al-O bonds, Al-L 23 edge fine structure is sensitive to the Al coordination, by which different aluminium oxide structures are usually characterized 28 . Amorphous aluminium oxides with different Al coordination have already been reported 26 29 30 . According to previous studies on the structure of materials containing Al-O bonds, the peak at ~77.6 eV in Al L 23 ELNES can serve as the fingerprint for tetrahedrally coordinated aluminium in the material 25 31 32 33 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In systems containing Al-O bonds, Al-L 23 edge fine structure is sensitive to the Al coordination, by which different aluminium oxide structures are usually characterized 28 . Amorphous aluminium oxides with different Al coordination have already been reported 26 29 30 . According to previous studies on the structure of materials containing Al-O bonds, the peak at ~77.6 eV in Al L 23 ELNES can serve as the fingerprint for tetrahedrally coordinated aluminium in the material 25 31 32 33 .…”
mentioning
confidence: 99%
“…The EEL spectrum from barrier oxide is consistent with that obtained from amorphous phase of Al 2 O 3 and different from crystalline phases 25 . However, the structure of the amorphous phase of aluminium oxide can vary significantly if the fabrication method or the size of the material is different 26 27 . In systems containing Al-O bonds, Al-L 23 edge fine structure is sensitive to the Al coordination, by which different aluminium oxide structures are usually characterized 28 .…”
mentioning
confidence: 99%
“…It was found that structural modifications involve changes in the fraction of the various Al-O coordination polyhedra that build the network structure. 35 However, in that latter study the fact that Al 2 O 3 cannot be transformed to a bulk glass did not allow for the comparison between the structure of the bulk glass and the 2D amorphous solid. In addition, interest arose recently on the 2D silica glass after the experimental 36,37 and theoretical investigations 38 of bilayer silica glass.…”
Section: Changes At the Short-and Medium-range Structural Order Ofmentioning
confidence: 96%
“…As thinner the film, higher the surface-to-volume ratio in film, therefore effect of the surface instability will be more significant: unconstrained bonds in surface are reported to be in high mobility of atoms, 2 and distinct coordination distributions in surface of amorphous Al 2 O 3 films affect the structural stability. 3 Besides, surface-originated instabilities were observed for many polymeric glasses. [4][5][6] Unfortunately, the underlying principles of structural stabilities of a-IGZO films remain unclear due to the difficulties encountered in experimental quantification.…”
mentioning
confidence: 99%
“…10 As m approaches 16, the glass is categorized as a relatively stable "strong glass", whereas larger values reveal a relatively unstable "fragile glass". We obtained m from the kinetics of the glass transition as: 11 m = E/(2.303 · RT g ) [ 3 ] where R is the gas constant and E is the activation energy of the glass transition at T = T g . E can be obtained using Moynihan's plot as 12…”
mentioning
confidence: 99%